The Repealed Prohibition of Baptism and Religious Marriage, Without the Previous State Process, Approval and Register - Riofrío Martínez-Villalba, Juan Carlos; Baquero de la Calle Rivadeneira, Jaime; Espinosa Quiroz, Pablo Marcelo; Aguilar González, Juan Pablo (Ius Humani. Jornal do direito, 2021)
This study explains how the Ecuadorian registry regulation has evolved related to the prohibition of celebrating baptism and religious marriage without having managed the identity registry and having carried out the civil marriage previously. Curiously, this prohibition was born in the Ecuadorian legal system with the advent of the secular State. From then, some constitutionalists experts observed that it was a contradiction to proclaim the separation of Church and State, allowing the State to control the sacraments of the Christian community by imposing prohibitions. Fortunately, the latest regulatory reforms of the Public Registry have eliminated such prohibition. However, some ecclesiastical sectors continue acting as if it still exists. These matters are analyzed with a casuistic, historical, and legal method that illustrates how the regulation had evolved and which is the current standard today. The analysis is divided into four sections. The first section identifies the problem and explains the current practices within the Catholic Church, despite the regulation changes. The second section describes certain cases where it is no longer convenient for the Church to require a civil certificate to officiate ecclesiastical ceremonies. The third section provides a historical and legal perspective of the Ecuadorian legislation. Finally, it is concluded that today the prohibition against celebrating baptism and religious marriage without the mediation of State registries has ceased to exist, and the Christian authorities are urged to review whether their practices can be better adapted to the new legal framework.